Flow dynamics for radiologists. II. Practical considerations in the live human. - Kerber, C W; Liepsch, D (American Journal of Neuroradiology, 1994)
Although the rules about flows seem complex and even at times suggest chaos, some general principles can be extracted and used by the radiologist. Normal arteries damp disturbances, tolerate our catheters well, and generally cause the blood's slipstreams to swirl. It seems that the swirls and the energy that accompanies the passage of those swirls are prime determiners of the development of degenerative changes, most importantly of atherosclerosis and berry aneurysms. Knowing this, we now must direct our research to look beyond today's practical applications and this simplistic summary. Radiologists who trained during the angiography era are often incredulous when they see the richness of information found in physiologic flow models. For years, contrast agents have hidden the elegant complexity of blood flow. Now, however, we have two new powerful machines: the Doppler gray-scale ultrasound and the MR scanner. These machines routinely demonstrate flow data that we do not as yet use. As angiographers we have a natural and unconscious bias to make images produced by our new machines look like the classic angiogram. It is a powerful and pervasive bias. We still call angiography our "gold standard." We must overcome that bias. As valuable as angiography has been to radiology, it may no longer be our benchmark. A new standard is ready to be developed. The MR scanner even now not only allows calculation of global flow in vessels but also analyzes individual slipstreams. The images shown here are only the beginning. Keep our old mindset, and the limits and utility of the MR scanner will not be explored by radiologists. However, if we physicians, especially radiologists, reenter the field of fluid dynamics, all of science and our patients will benefit. We have broad shoulders to stand on and see into the future. Harvey, Hales, Galen, and Poiseuille: all were physicians; they added immeasurably to the foundations of rheology and our understanding of flowing blood. We must be willing to do likewise.